Exploring coupling effects of rainfall and surface roughness on the sheet flow velocity - Enshuai Shen; Gang Liu; Qiong Zhang; Chenxi Dan; Chang Liu; Hairu Li; Ya Liu; Xueming Qu; Xiaolin Xia; Dandan Liu; Zhen Guo; Xining Zhao (International Soil and Water Conservation Research)
Accurately describing the path of sheet flow (SF) is crucial in soil erosion. Raindrop impact and underlying surface conditions can affect the SF velocity by changing the velocity profile. However, since this information is rarely known, the estimation of SF velocity is inaccurate. A series of upstream inflow and rainfall experiments were carried out on an impermeable flume to determine the coupling effects of rainfall and rough bed surfaces on the SF velocity and correction factor (α). The results showed that the roughness of the bed surface had a more pronounced effect on reducing the mean velocity compared to the surface velocity in both cases with and without raindrop impact. The raindrop impact notably reduced the flow velocity near the water surface, while the mean velocity slightly decreased or remained almost constant with increasing rainfall intensity. The reduction in SF velocity can be explained by the combined effects of the roughness reducing the mean velocity (up to 33.52%) and the raindrop impact reducing the surface velocity (up to 25.43%). In addition, α was not a constant when the SF was subjected to raindrop impact. The rainfall was found to increase α, while the roughness of the bed surface reduced α for all cases. Finally, a model was created to forecast α based on the ratio of water depth to roughness height, hydraulic slope, and rain Reynolds number. The results are valuable in soil erosion by providing accurate α for estimating the surface and mean velocities of SF.